Effects of different levels of urea and magic growth spray solution on the yield and yield attributes of BRRI dhan29 (Research in Agriculture Livestock and Fisheries, 2016)
Magic growth solution along with prilled urea in the rice leaf as foliar spray may save urea compared to soil application of urea alone. In this regard, an experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University during Boro Season (December-April, 2015) to evaluate the effects of urea and magic growth spray solution on the yield and yield attributes of BRRI dhan29. The experiment consisted of ten treatments viz.,T1 = Control, T2 = 99 kg urea ha-1, T3 = 63 kg urea ha-1 + 2.16L ha-1 magic growth spray solution, T4 = 99 kg urea ha-1 + 5.66L ha-1 magic growth spray solution, T5 = 117 kg urea ha-1 + 1.44L ha-1 magic growth spray solution, T6 = 117 kg urea ha-1 + 5.66L ha-1 magic growth spray solution, T7 = 126kg urea ha-1 + 5.66L ha-1 magic growth spray solution,T8 = 132 kg urea ha-1, T9 = 132 kg urea ha-1 + 5.66L ha-1 magic growth spray solution, T10= 132 kg urea ha-1+ 2.16L ha-1 magic growth spray solution and laid out in a randomized complete block design (RCBD) with three replications. The results revealed that urea and magic growth spray solution exerted significant influence on the yield contributing characters and yield of BRRI dhan29 except panicle length, sterile spikelets and 1000-grain weight. The highest grain and straw yields (6.16 and 9.33 t ha-1, respectively) were obtained from T7 treatment which could be the resultant effect of highest number of effective tillers hill-1, highest number of grains panicle-1 and lowest number of sterile spikelets panicle-1. Grain yield was significantly and positively correlated with plant height, effective tillers hiil-1, panicle length and grains per panicle. Economic analysis showed that net return and benefit cost ratio (BCR) was the highest (1.41) in T7 treatment. Thus the overall results suggest that farmers may be advised to apply 126 kg urea along with 5.66L magic growth solution per hectare to produce economically highest grain yield of BRRI dhan29, under the agro-climatic condition of Bangladesh Agricultural University.Res. Agric., Livest. Fish.3(2): 271-278, August 2016